PENGARUH CORPORATE GOVERNANCE TERHADAP VOLUNTARY AUDITOR SWITCHING (Studi Empiris pada Perusahaan Manufaktur, Perdagangan, Jasa, dan Investasi yang Terdaftar di Bursa Efek Indonesia pada Tahun 2009 - 2013) - Muhammad Habib Takeshi Johari; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2015)
This research aims to examine and obtain empirical evidence about the elements of corporate governance mechanism that affect the replacement of public accountant on a voluntary basis in Indonesia. This issue is important because the company raised given the freedom to choose the auditor and replace it outside the rules (mandatory). Independent variables that used in this research : managerial ownership, concentration of ownership, change of directors, the composition of the board of commissioners, audit committee size, and the number of audit committee meetings. The object of this research are firms on the sector of manufacturing, trade, services and investments listed in the Indonesian Stock Exchange during the five years (2009-2013) but for some variables needed data in previously. Data collection method used in this research is purposive sampling, based on predetermined criteria. A total of 45 companies per year, is used as sample company. Data were analyzed using logistic regression analysis. Results from this research showed that the concentration of ownership and the number of audit committee meetings per year, have a positive influence on voluntary auditor switching. The next result shows that managerial ownership and the size of the audit committee have a negative effect on voluntary auditor switching. While the other variables examined in this research as the change of the directors and the composition of the board of commissioners are not shown to have an influence on the company's decision to do voluntary auditor switching.